Monitoring Kesehatan Struktur Rangka Gedung Tidak Beraturan Berdasarkan Hasil Sensor Akselerometer - Darmawan, Wan Fikri; Suryanita, Reni; Djauhari, Zulfikar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Indonesian especially those in urban areas, currently actively undertaking development in various fields especially building construction. If the building is not maintained during the designated life of the plan, then the resistance of the structure of the building will quickly decrease and cause the building will quickly be damaged. Therefore, one of the solutions for maintaining structural resistance required building inspection by using accelerometer sensor. Result of recordings accelerometer sensor will be used as a reference in determining structural damage, so it can determine healthy from structure. This research is obtained to give information response structure from accelerometer data. Structural damage can determine using the equations developed by Jer Fu Wang, Chi Chang, and Shih Min. The building model is irregular reinforced concrete with three levels and height between level is 3,5 m. Building model will receive a dynamic loads from the results of accelerometer sensor. The vibration data used is June 4 and December 11 of 2016 at 06.00, 12.00, 18.00 WIB. The vibration data will be input for building model in doing the linear time history analysis and static nonlinear pushover by using the software finite element. From the analysis, maximum structure behavior is 11 December 2016 at 12.00 WIB. The value of stiffness for pushover analysis in the first step is 5,454, the second step is 5,243, the third step is 5,477, and the fourth step is 5,560. The value of stiffness for linear time history is 5,599. The value of SDI (Story Damage Index) in the first step is 0,026, the second step is 0,064, the third step 0,022 and the fourth step is 0,007. From the results of this SDI, the irregular reinforced concrete building is still in healthy condition.Keywords: accelerometer sensor, structural damage, structural health monitoring